Optical doping and damage formation in AIN by Eu implantation - Lorenz, K. (2012)
AlN films grown on sapphire were implanted with 300 keV Eu ions to fluences from 3×1014 to 1.4×1017 atoms/cm2 in two different geometries: “channeled” along the c-axis and “random” with a 10° angle between the ion beam and the surface normal. A detailed study of implantation damage accumulation is presented. Strong ion channeling effects are observed leading to significantly decreased damage levels for the channeled implantation within the entire fluence range. For random implantation, a buried amorphous layer is formed at the highest fluences. Red Eu-related photoluminescence at room temperature is observed in all samples with highest intensities for low damage samples (low fluence and channeled implantation) after annealing. Implantation damage, once formed, is shown to be stable up to very high temperatures.